A Specific Reduction in Aβ1−42 vs. a Universal Loss of Aβ Peptides in CSF Differentiates Alzheimer's Disease From Meningitis and Multiple Sclerosis - Spitzer, Philipp; Lang, Roland; Oberstein, Timo J.; Lewczuk, Piotr; Ermann, Natalia; Huttner, Hagen B.; Masouris, Ilias; Kornhuber, Johannes; Ködel, Uwe; Maler, Juan M. (Frontiers in Aging Neuroscience, 2018)
A reduced concentration of Aβ1-42 in CSF is one of the established biomarkers of Alzheimer’s disease. Reduced CSF concentrations of Aβ1-42 have also been shown in multiple sclerosis, viral encephalitis and bacterial meningitis. As neuroinflammation is one of the neuropathological hallmarks of Alzheimer’s disease, an infectious origin of the disease has been proposed. According to this hypothesis, amyloid pathology is a consequence of a microbial infection and the resulting immune defense. Accordingly, changes in CSF levels of amyloid-β peptides should be similar in AD and inflammatory brain diseases. Aβ1-42 and Aβ1-40 levels were measured in cerebrospinal fluid by ELISA and Western blotting in 34 patients with bacterial meningitis (n=9), multiple sclerosis (n=5) or Alzheimer’s disease (n=9) and in suitable controls (n=11). Reduced concentrations of Aβ1-42 were detected in patients with bacterial meningitis, multiple sclerosis and Alzheimer’s disease. However, due to a concurrent reduction in Aβ1-40 in multiple sclerosis and meningitis patients, the ratio of Aβ1-42/Aβ1-40 was reduced only in the CSF of Alzheimer’s disease patients. Urea-SDS-PAGE followed by Western blotting revealed that all Aβ peptide variants are reduced in bacterial meningitis, whereas in Alzheimer’s disease, only Aβ1-42 is reduced. These results have two implications. First, they confirm the discriminatory diagnostic power of the Aβ1-42/Aβ1-40 ratio. Second, the differential pattern of Aβ peptide reductions suggests that the amyloid pathology in meningitis and multiple sclerosis differs from that in AD and does not support the notion of AD as an infection-triggered immunopathology.